2017
DOI: 10.1089/gtmb.2016.0219
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Interleukin-27 Genetic Variants on Atrial Fibrillation Susceptibility

Abstract: Our findings indicated that the IL-27 genetic polymorphisms may be associated with susceptibility of AF in Chinese Han population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 22 publications
0
10
0
1
Order By: Relevance
“…The association between inflammation and AF has been shown in both animal models and human studies [7], demonstrating increased levels of inflammatory biomarkers such as high-sensitivity C-reactive protein, PTX3, IL-6 [15], as well as IL-27 [16]. It has been shown that high plasma levels of IL-6 are not just correlated with the presence and duration of AF but also with an increased left atrial diameter [17].…”
Section: Resultsmentioning
confidence: 98%
“…The association between inflammation and AF has been shown in both animal models and human studies [7], demonstrating increased levels of inflammatory biomarkers such as high-sensitivity C-reactive protein, PTX3, IL-6 [15], as well as IL-27 [16]. It has been shown that high plasma levels of IL-6 are not just correlated with the presence and duration of AF but also with an increased left atrial diameter [17].…”
Section: Resultsmentioning
confidence: 98%
“…Previous studies showed that rs153109, rs17855750 and rs181206 of IL27 gene displayed significant associations with dilated cardiomyopathy (DCM) (33), atrial fibrillation (AF) (33), allergic rhinitis (34), pre-eclampsia (35) and renal cell carcinoma (RCC) (36). Thyroid autoimmunity is frequently related to polyglandular endocrine syndromes (37, 38).…”
Section: Discussionmentioning
confidence: 99%
“…Previous clinical studies have reported that elevated IL-12 expression is observed in left atrial tissues of atrial fibrillation patients (Stein et al, 2008;Lappegård et al, 2013). Chen et al found that IL-27 genetic variants, including the rs153109 G allele and GG genotype, increased the occurrence of atrial fibrillation in the Chinese Han population (Chen et al, 2017a).…”
Section: Interleukin-12 Family Members and Atrial Fibrillationmentioning
confidence: 99%